STUDY OF ELECTRONS ENERGY RESOLUTION, IN CMS (LHC) EXPERIMENT USING SIMULATED DATA - Hayrapetyan, A.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2020)
This work is dedicated to the study of the energy resolution of electrons using simulated data of “Drell-Yan” process with \( e^-e^+ \) yield in \(pp\)‑interactions at \( s=13 TeV \). The work contains a brief description of event modeling and electron reconstruction from the simulated data. The energy resolution was estimated from the distribution of the ratio of the transverse energies of reconstructed and generated electrons. Two approaches used in calculations. In the first approach, the standard definition of energy resolution was used (Full width at half maximum – FWHM), and in the second, the root mean square of distribution was taken as a describing value for energy resolution.